2016
DOI: 10.1007/s11157-016-9398-6
|View full text |Cite
|
Sign up to set email alerts
|

Abandoned metalliferous mines: ecological impacts and potential approaches for reclamation

Abstract: The lack of awareness for timely management of the environment surrounding a metal mine site results in several adverse consequences such as rampant business losses, abandoning the bread-earning mining industry, domestic instability and rise in ghost towns, increased environmental pollution, and indirect long-term impacts on the ecosystem. Although several abandoned mine lands (AMLs) exist globally, information on these derelict mines has not been consolidated in the literature. We present here the state-of-th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(56 citation statements)
references
References 218 publications
0
48
0
Order By: Relevance
“…However, given the long history of mining in Africa (both legal and illegal Artisanal mining), mine wastelands are predicted to cover large areas. For instance, Venkateswarlu et al (2016) reported ca. 6150 officially listed abandoned mines in South Africa alone, with areas contaminated by toxic and radioactive mine residues in Gauteng province, a known source of gold ore, covering 321 km 2 .…”
Section: Restoration Research and Practice In Africamentioning
confidence: 99%
See 1 more Smart Citation
“…However, given the long history of mining in Africa (both legal and illegal Artisanal mining), mine wastelands are predicted to cover large areas. For instance, Venkateswarlu et al (2016) reported ca. 6150 officially listed abandoned mines in South Africa alone, with areas contaminated by toxic and radioactive mine residues in Gauteng province, a known source of gold ore, covering 321 km 2 .…”
Section: Restoration Research and Practice In Africamentioning
confidence: 99%
“…The most notable impact of mining is the change in land form caused by clearing of vegetation, removal of topsoil and disposal of large amounts of waste. Mine wastes usually include waste rock, overburden, slag, and tailings on land surfaces, while mine wastelands are comprised of stripped areas, open-pits, loose soil piles, waste rock and overburden surfaces, subsided lands, tailings dams and other lands degraded by mining facilities (Wong 2003;Li 2006;Sikaundi 2013;Venkateswarlu et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Contamination by heavy metals or radiation in unreclaimed or inadequately reclaimed sites can significantly limit post-mining land use potentials [21,137,138]. Compared to metal mines, quarries (mines which produce building materials and dimensional stone) tend to have more versatile post-mining options, because they usually have less hazardous wastes and are located closer to densely populated areas [28,139,140].…”
Section: Restrictions and Hazards Related To Post-mining Land Usementioning
confidence: 99%
“…Further, abandoned or inadequately closed mines may continue to degrade surrounding land, water bodies and air [19][20][21]. Globally, there is a huge number of mines where acceptable mine closure did not take place or was incomplete [5,6,[22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…At the end of the mining activity, about 6.500 hectares were abandoned, with no attention being paid to environmental and social changes (Rocha-Nicoleite et al, 2013;Rocha-Nicoleite, 2015;Rocha-Nicoleite, 2017). Similar situations have occurred in other mining areas around the world (Bell et al, 2001;Johnson, 2001;Cravotta, 2008;Mishra et al, 2012;Gutiérrez et al, 2016;Kim et al, 2016;Venkateswarlu et al, 2016;Bailey & Hooey, 2017;Merem et al, 2017).…”
Section: Introductionmentioning
confidence: 98%